"Ten and Under Tennis" for ALL Ages!: Editor: Ferman Konukman. Issue 4 (3rd May 2020) - Flick, Lori
Abstract : The United States Tennis Association (USTA) began an initiative that encouraged professionals to teach tennis using a modified method to students ten years of age and under. Termed "Ten and Under Tennis, " "QuickStart, " and now, currently modified to include students 5–18 years of age, "Net Generation, " this adaptable system aims to teach toward the development and lifelong participation of beginning youth players. Variations of this teaching methodology were also expanded to teach all ages of beginning tennis students, including young adults, yielding positive results.